Laccaria rubroalba sp. nov. (Hydnangiaceae, Agaricales) from Southwestern China - Luo, Xia; Ye, Lei; Chen, Jie; Karunarathna, Samantha C.; Xu, Jianchu; Hyde, Kevin D.; Mortimer, Peter E. (Phytotaxa, 2016)
The novel species Laccaria rubroalba is described from Southwestern China by using both morphological characteristics and molecular data. It is characterized by small basidiomata; reddish white pileus when moist or young, white to pale when dry; 4-spored basidia and globose to broadly ellipsoid, hyaline, moderately echinulate basidiospores. Phylogenetic relationships inferred from ITS sequence data confirmed the separation of this new species from other closely related species in the genus Laccaria. The new species is compared with similar taxa. A description, line drawings and colour photographs of the new species, and phylogenetic tree to show the placement of the new species are provided.